Conservation of Tibetan Sheep endangered species of Sikkim-Himalayas - Kumar, Brijesh; Avasthe, R. K.; Bhutia, Karma T. (Indian Farming, 2018)
Without doubt, sheep rearing is a profitable venture and most sustainable in alpine agro-ecosystem yet it has failed to attract younger generations. Besides, absence of proper policy is leading to rapid decline of Tibetan sheep population in this valley. The valley had a population of around thousand sheep upto two years ago whereas now it is only 230. It is very much alarming for the existence of this valuable sheep germplasm. Recently ICAR Research Complex, Sikkim Centre in collaboration with National Bureau of Animal Genetic Resources. Karnal,has almost completed characterization of Tibetan sheep and motivated the shepherd to start year round breeding with improved managemental practices. In view of the high agro-ecological and livelihood significance the Tibetan sheep deserves urgent in situ and exsitu species conservation measures to arrest its extinction.